STRATEGIES AND EDUCATIONAL CHALLENGES FOR THE MILLENNIAL GENERATION - Siti Afifatun (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2025)
This article aims to describe appropriate strategies and educational challenges for the millennial generation. The type of research is descriptive analytical, namely describing and analyzing problems using expert theories about values ??education from an Islamic perspective. The millennial generation is the generation born between 1980-2000. They have the characteristics of liking to rely on the speed of instant (ready-to-eat) information, liking existence, liking opinions, growing their image, broadening their insight, liking freedom, liking personalization, liking learning, working in an innovative environment, actively collaborating, hyper technological, critical, confident, connected, lazy, not deep, not grounded, or less social. The results of the research state that the strategy from an Islamic perspective is to teach values ??to the Millennial Generation, including rahmatan lil alamin/compassion, instilling deeper values ??in the Qur'an and Hadith, instilling local wisdom values ??and so on.